Spontaneous Resolution of Pulmonary Nodules in Autoimmune Pancreatitis - Goldsmith, Paul J; Cockbain, Andrew J; Smith, Andrew M (JOP. Journal of the Pancreas, 2010)
Context Autoimmune pancreatitis is a rare benign disorder that can be confused with pancreatic cancer and the treatment pathway differs dramatically. Case report We present a unique case of pulmonary nodules associated with autoimmune pancreatitis, that was initially confused for pancreatic cancer which resolved spontaneously. Herein we describe the case and subsequent management and discuss the ever increasing incidence of autoimmune pancreatitis. Conclusion Pulmonary nodules associated with equivocal CT findings of primary pancreatic cancer should be treated with suspicion that the primary diagnosis may be incorrect and other differential diagnoses should be explored. Image: Pulmonary nodules on computerised tomography.